Cabozantinib Versus Sunitinib for Untreated Patients with Advanced Renal Cell Carcinoma of Intermediate or Poor Risk: Subgroup Analysis of the Alliance A031203 CABOSUN trial. (9th August 2019) - George, Daniel J.; Hessel, Colin; Halabi, Susan; Michaelson, M. Dror; Hahn, Olwen; Walsh, Meghara; Picus, Joel; Small, Eric J.; Dakhil, Shaker; Feldman, Darren R.; Mangeshkar, Milan; Scheffold, Christian; et al.
Abstract: Cabozantinib treatment prolonged progression‐free survival (PFS) and improved objective response rate (ORR) compared with sunitinib in patients with advanced renal cell carcinoma (RCC) of intermediate or poor risk by International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) criteria in the phase II CABOSUN trial (NCT01835158). In the trial, 157 patients were randomized 1:1 to receive cabozantinib or sunitinib, stratified by IMDC risk group and presence of bone metastases. Here, PFS and ORR, both determined by independent radiology committee (IRC), were analyzed by subgroups of baseline characteristics. Cabozantinib treatment was generally associated with improved PFS and ORR versus sunitinib across subgroups, including in groups defined by IMDC risk group, bone metastases, age, and tumor burden. Clinical trial identification number . NCT01835158. Abstract : The phase II CABOSUN trial compared cabozantinib with sunitinib as initial treatment in patients with advanced renal cell carcinoma of intermediate or poor risk. This article presents subgroup analyses by baseline patient characteristics.